Windfall gains and stock market participation - Briggs, Joseph; Cesarini, David; Lindqvist, Erik; Östling, Robert (Journal of Financial Economics, 2021)
We exploit the randomized assignment of lottery prizes in a large administrative Swedish data set to estimate the causal effect of wealth on stock market participation. A $150,000 windfall gain increases the stock market participation probability by 12 percentage points among prelottery nonparticipants but has no discernible effect on prelottery stock owners. A structural life cycle model significantly overpredicts entry rates even for very high entry costs (up to $31,000). Additional analyses implicate pessimistic beliefs regarding equity returns as a major source of this overprediction and suggest that both recent and early-life return realizations affect beliefs.